2019
DOI: 10.1186/s12887-019-1479-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between anxiety and aggression in adolescents: a cross-sectional study

Abstract: Background The purpose of this study was to investigate the relationship between anxiety proneness and aggressive behavior in adolescents. Methods A quantitative, large scale cross-sectional study was conducted in Korea. The survey questionnaire included general health behavior and scales for assessing anxiety (Revised Children’s Manifest Anxiety Scale; RCMAS) and aggressive behavior (The Aggression Questionnaire; AQ) in adolescents. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 36 publications
8
34
0
1
Order By: Relevance
“…Moreover, among the surveyed women, significantly higher rates of anger and hostility, two of the four components of generalized aggression, were observed. This is consistent with the majority of global observations [ 35 , 36 ]. However, a study conducted during the COVID-19 pandemic in China showed the same severity of anxiety in both women and men [ 37 ], which may contribute to the consideration of intercultural differences or specific situations regarding pandemic and lockdowns.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, among the surveyed women, significantly higher rates of anger and hostility, two of the four components of generalized aggression, were observed. This is consistent with the majority of global observations [ 35 , 36 ]. However, a study conducted during the COVID-19 pandemic in China showed the same severity of anxiety in both women and men [ 37 ], which may contribute to the consideration of intercultural differences or specific situations regarding pandemic and lockdowns.…”
Section: Discussionsupporting
confidence: 93%
“…Often, a lack of self-knowledge, poor coping skills, and a greater sensitivity to being influenced by external events leads to a mismanagement of events and the feeling of losing one's goals [59]. Moreover, some researchers have suggested a strong association between aggression and anxiety [60,61]; it could be hypothesized that having adaptive responses to anxiety to cope with the personal stress caused by restrictive measures can also be useful in dealing with the spread of the epidemic [62][63][64].…”
Section: Discussionmentioning
confidence: 99%
“…Anger and hostility indicate the affective and cognitive facets of aggression, while physical and verbal aggression constitute the (Reyna et al, 2011;Chung et al, 2019). Adolescents with ADHD, unlike children with ADHD, show less hyperactivity and more internal problems, such as frustration and low self-esteem (Cantwell, 1996;Dupaul, 1991;Jeong et al, 2001).…”
Section: Discussionmentioning
confidence: 99%